Middle Cerebral Artery Pulsatility Index as Predictor of Cognitive Impairment in Hypertensive Patients - Harris, Salim; Reyhan, Teuku; Ramli, Yetty; Prihartono, Joedo; Kurniawan, Mohammad (Frontiers in Neurology, 2018)
Background: Cognitive impairment is a manifestation of cerebrovascular disease regarding hypertension and other degenerative diseases which has become a global health issue due to increased life expectancy. Recently, gold standard used for diagnosing vascular cognitive impairment (VCI) requires a combination of neurophysiological approach and magnetic resonance imaging (MRI). Neurosonological approach by measuring pulsatility index (PI) of the middle cerebral artery (MCA) using Trans Cranial Doppler (TCD) hopefully can be used as an affordable alternative predictor of VCI in patients with hypertension. Methods: A cross-sectional study was conducted at Outpatient Clinic of Department of Neurology in Ciptomangunkusumo Hospital, Jakarta. Sixty-six hypertensive subjects with no macrovascular complication were selected and screened using Montreal Cognitive Assesment-Indonesia version (MoCA-Ina) to determine their cognitive status. Subjects were categorized into two groups; subjects with scores ≥26 were classified as normal cognitive group, while subjects with scores <26 were classified as cognitive impairment group. Both groups then underwent TCD examination to determine bilateral MCA PI. Results: There was a significant difference between MCA PI in both groups; it was higher in cognitive impairment group than normal group (p<0.001). Subjects with increased left MCA PI were more likely to suffer cognitive impairment than those with increased right MCA PI. Conclusion: MCA PI can be used as a predictor for cognitive impairment in hypertensive subjects.